Bordering on Empathy: The Effect of Selective Exposure and Border Residency on Immigration Attitudes. Issue 3 (3rd July 2019) - Price, Debra Muller; Kaufhold, Kelly
Abstract : Two surveys, including an original survey and a survey containing substantial secondary data, found substantial links between party identity, selective media exposure and attitudes on immigration. Republicans were significantly more likely to segregate themselves to like-minded media and to avoid traditional objective sources like national and local newspapers, local and national broadcast television news. Border-state residency failed to moderate attitudes about immigration; differences were found between local and national media. Finally, Republican support for immigration fell between 2016 and 2018, after the election of President Trump.